“Authenticity” and “foreign talent” in Singapore : the relative and negative logic of national identity - Yang, Peidong (2014)
Singapore’s constitutive sociocultural hybridity has meant that this postcolonial island-nation’s national identity has always been a problematic construct. The developmental state’s pragmatism and self-re-inventiveness further undermine the efforts to construct a stable national identity, frustrating the desire for an authentic nationhood in the essentialist and positive sense. Focus on the more recently arrived “foreign talent” subjects who inhabit the margins of the Singaporean imagination of the national body informs an alternative analytical angle on the question of Singaporean national identity. It is suggested that a sense of national togetherness and belonging emerges through constructing these national Others as “inauthentic”. Examination of two particularly visible and controversial types of “foreign talent” in Singapore — foreign sports professionals and foreign students who have received scholarships from the Singapore government — and of the ways in which they are discursively framed suggests that the “foreign talent” unwittingly constitute a relative and negative solution to Singapore’s national identity problem.